African Multilingualisms Rural Linguistic and Cultural Diversity - Di Carlo, Pierpaolo; Good, Jeff; Akumbu, Pius W.; Assomo, Célestine G.; Atindogbé, Gratien G.; Chenemo, Margaret; Chie, Esther P.; Cobbinah, Alexander Yao; Dissake, Endurence M. K.; Agwara, Angiachi D. Esene; Goron, Amina N.; Makon, Marguérite G.; et al. (Lexington Books, 2020)
African Multilingualisms is the first book dedicated to presenting case studies of small-scale multilingualism in rural Africa. Contributors present extensive new data on sociolinguistic patterns found in these contexts and consider new, more ethnographically sensitive methods for exploring multilingualism of this kind.